Sustainable Tourism from Architectural Perspective: A Literature Review - Saufa Yardha Moerni (Syntax Corporation, 2023)
This article discusses the main concept of sustainable tourism to comprehend the terminology on definition, aspects, and main concept. Furthermore, the discussion continues how architecture plays an important part in achieving the sustainability of tourist attraction areas, and the practical ways that have been done from an architectural perspective. The discussion on the architecture subject is divided into 2 parts: the heritage buildings and new buildings, and how the architectural decision in those areas plays a part in supporting sustainable tourism. In heritage building tourism, it is important to ensure the building is in good condition physically and functional. Adaptive reuse is mainly being used to revitalize heritage buildings. In new buildings, several ways can be done to support sustainability in tourism and it's usually by designing an environmentally low negative impact building's design. If these strategies are applied in building design, it is possible to develop a tourism area that emphasizes the concept of sustainability.